Pengaruh Fashion Influencer terhadap Sikap Merek dan Niat Beli Konsumen - Alfinaldi, Athariq; Astuti, Budi (Universitas Hamzanwadi, 2023)
The impact of fashion influencers on brand perception and customer desire to buy is explored. This study seeks to answer the following research questions about the relationship between consumer attitudes toward influencers and consumer brand attitudes: do consumer attitudes toward influencers influence brand attitudes? do consumer brand attitudes and consumer attitudes toward influencers have a positive effect on purchases? In this study, a quantitative methodology was employed. In order to gather information, we sent out 150 surveys. The results of the SEM-PLS analysis show that perceived credibility, trust, subjective norms, perceived influencer expertise, Positive and substantial correlations are found between brand attractiveness and attitudes and attitudes toward influencers. Meanwhile, consumer views about influencers are unaffected by behavioral control and perceptual conformity. favorable consumer views about influencers have a big and favorable impact on those consumers' positive sentiments toward companies and their intentions to make a purchase. Marketers who leverage fashion influencers might, therefore, utilize the findings of this study to inform future marketing strategies